Spider assemblages in Rimba Ilmu Botanical Garden, Kuala Lumpur, Malaysia - Dzulhelmi, M.N.; Norma-Rashid, Y. (Universiti Kebangsaan Malaysia, 2014)
The seasonal variation of spider assemblages in botanical garden was investigated. The spiders were manually collected by diurnal and nocturnal session between two seasons. A total of 19 families from 65 genera and 96 species were recorded. Richness-estimator indicates the inventory were 67% complete within the botanical garden. The capture rate for web-weavers were higher compared with non-web weavers. The comparison value showed the species composition and abundance were similar between seasons. Spider abundance was not affected between wet and dry season in tropical countries.